Occupational Risk Factors for COPD Phenotypes in the Multi-Ethnic Study of Atherosclerosis (MESA) Lung Study - Doney, Brent (2014)
INTRODUCTION: The contribution of occupational exposure to the risk of chronic obstructive pulmonary disease COPD in population-based studies is of interest. We compared the performance of self-reported exposure to a newly developed JEM in exposure-response evaluation. METHODS: We used cross-sectional data from Multi-Ethnic Study of Atherosclerosis (MESA), a population-based sample of 45–84 year olds free of clinical cardiovascular disease at baseline. MESA ascertained the most recent job and employment, and the MESA Lung Study measured spirometry, and occupational exposures for 3686 participants. Associations between health outcomes (spirometry defined airflow limitation and Medical Research Council-defined chronic bronchitis) and occupational exposure [self-reported occupational exposure to vapor-gas, dust, or fumes (VGDF), severity of exposure, and a job-exposure matrix (JEM)-derived score] were evaluated using logistic regression models adjusted for non-occupational risk factors. RESULTS: The prevalence of airflow limitation was associated with self-reported exposure to vapor-gas (OR 2.6, 95%CI 1.1–2.3), severity of VGDF exposure (P-trend<0.01), and JEM dust exposure (OR 2.4, 95%CI 1.1–5.0), and with organic dust exposure in females; these associations were generally of greater magnitude among never smokers. The prevalence of chronic bronchitis and wheeze was associated with exposure to VGDF. The association between airflow limitation and the combined effect of smoking and VGDF exposure showed an increasing trend. Self-reported vapor-gas, dust, fumes, years and severity of exposure were associated with increased prevalence of chronic bronchitis and wheeze (P<0.001). CONCLUSIONS: Airflow limitation was associated with self-reported VGDF exposure, its severity, and JEM-ascertained dust exposure in smokers and never-smokers in this multiethnic study.